2021
DOI: 10.3346/jkms.2021.36.e100
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects between COVID-19 Outbreak and Community Income Levels on Excess Mortality among Patients Visiting Emergency Departments

Abstract: Background The objective of this study was to examine the effect of the coronavirus disease 2019 (COVID-19) outbreak on excess in-hospital mortality among patients who visited emergency departments (EDs) and to assess whether the excess mortality during the COVID-19 pandemic varies by community income level. Methods This is a cross-sectional study using the National Emergency Department Information System (NEDIS) database in Korea. The study population was defined as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…During the study period from 2016 to 2019, the participation rate of nationwide EDs in the NEDIS was 408 of 413 (98.8%) EDs in 2016, 413 of 416 (99.3%) EDs in 2017, 399 of 401 (99.5%) EDs in 2018, and 401 of 402 (99.8%) EDs in 2019. The detailed design and variables of the NEDIS database have been described elsewhere [ 23 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the study period from 2016 to 2019, the participation rate of nationwide EDs in the NEDIS was 408 of 413 (98.8%) EDs in 2016, 413 of 416 (99.3%) EDs in 2017, 399 of 401 (99.5%) EDs in 2018, and 401 of 402 (99.8%) EDs in 2019. The detailed design and variables of the NEDIS database have been described elsewhere [ 23 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inaccurate data is filtered by a data processing system. The NEDIS data is updated in real time by the National Emergency Medical Center and approved annually by National Statistics for data quality management [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…It may be due to general hesitancy or ED transport refusal among patients [ 43 , 44 ] and limited resources under new policies [ 24 ]. Although there were no significant differences in disease-related ED mortality by year, the increasing number of total deaths, length of stay, and proportion of patients with KTAS levels 1–2 is in line with worsening mortality in Korea which is affected by the collateral damage of COVID-19 [ 25 ]. Our finding that 63.5% of ED visitors had cancer supports a Taiwanese study that reported cancer patients visited EDs more frequently near EOL, possibly due to high national health insurance coverage [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the coronavirus disease of 2019 (COVID-19) pandemic has also imposed strict quarantine policies such as large-scale screening for viral symptoms and visitor restrictions [ 18 ], thus making the ED more unsuitable for death [ 19 , 20 ]. Although the total number of ED visitations decreased during the pandemic in the United States [ 21 , 22 ] and Korea [ 23 , 24 ], the ED mortality rate significantly increased after COVID-19 in Korea [ 25 ]. Hence, there is growing interest in providing and even initiating palliative care for terminal patients in ED [ 26 – 30 ].…”
Section: Introductionmentioning
confidence: 99%